Effect of Aerobic and Resistance Exericse for Cardiometabolic Profil for Obesity Person: Critical Review - Rahman, Farid; Vionita, Yulia; Susanti, Yulis; Budi, Ilham Setya (Ikatan Fisioterapi Indonesia, 2022)
The prevalence of obesity has increased significantly globally and is considered a severe public health problem in the coming decades. Obesity can increase the risk of morbidity and mortality of cardiometabolic disease (metabolic syndrome). Combining aerobic exercise and resistance training can improve the cardiometabolic profile associated with metabolic syndrome markers. This study aims to determine whether a combination of aerobic exercise and resistance training affects the cardiometabolic profile of obese individuals. The design of this research study used a critical review with a Randomized Controlled Trial (RCT). A critical review study was conducted by appraising the selected articles using the PEDro scale. The PEDro scale score was obtained with a score of 7/10; there were two articles, 6/10 were two articles, 5/10 had 1 article, and 4/10 were two articles. The combination of aerobic exercise and resistance training affects the cardiometabolic profile (triglyceride levels, high-density lipoprotein cholesterol, low-density lipoprotein, glucose intolerance) in obese individuals compared to just being given aerobic exercise or resistance training alone. Providing a combination of aerobic exercise and resistance training can improve cardiometabolic profile (triglyceride levels, high-density lipoprotein cholesterol, low-density lipoprotein cholesterol, glucose intolerance) in obese individuals with the recommendation of exercise is aerobic exercise (treadmill) with an intensity of 40-85% of the maximum. Heart Rate (HRmax) 3 times per week for at least 30 minutes. While resistance training (lifting exercises for upper limb limbs and lower limb with an intensity of 60-80% of 1 Repetition Maximum (1RM) 3 times per week, two sets, 8-10 reps, rest 1-2 minutes, and the exercise is done for at least 30 minutes.